2023
DOI: 10.1109/tnsre.2023.3237319
|View full text |Cite
|
Sign up to set email alerts
|

ST-CapsNet: Linking Spatial and Temporal Attention With Capsule Network for P300 Detection Improvement

Abstract: A brain-computer interface (BCI), which provides an advanced direct human-machine interaction, has gained substantial research interest in the last decade for its great potential in various applications including rehabilitation and communication. Among them, the P300-based BCI speller is a typical application that is capable of identifying the expected stimulated characters. However, the applicability of the P300 speller is hampered for the low recognition rate partially attributed to the complex spatio-tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Lawhern et al [27] developed EEGNet, a compact CNN-based DNN that can analyze and classify brain signals from various mental activities. Additionally, there have been improved versions of EEGNet, such as the one by Zhang et al [28] for detecting single-trial P300 signals, as well as new DNN architectures like ST-CapsNet [29], which integrates spatial and temporal attentions using a capsule network for P300 detection, and a CNN-based approach by Du et al [30] that classifies single-trial P300 signals by fusing data from multiple subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Lawhern et al [27] developed EEGNet, a compact CNN-based DNN that can analyze and classify brain signals from various mental activities. Additionally, there have been improved versions of EEGNet, such as the one by Zhang et al [28] for detecting single-trial P300 signals, as well as new DNN architectures like ST-CapsNet [29], which integrates spatial and temporal attentions using a capsule network for P300 detection, and a CNN-based approach by Du et al [30] that classifies single-trial P300 signals by fusing data from multiple subjects.…”
Section: Introductionmentioning
confidence: 99%
“…In EEG-BCIs, signals can be classified into evoked and spontaneous types. Evoked EEG involves triggering specific brain responses through external stimuli, such as P300 [20][21][22][23] and Steady-State Visual Evoked Potentials (SSVEPs) [24][25][26][27][28][29]. While extensively studied in BCI systems, P300 is susceptible to interference and prolonged fixation on light sources, while SSVEPs may lead to visual fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…Macías-Macías et al ( 2022 ) introduced a capsule neural network that has shown promising P300 classification performance with small samples and few channels. Furthermore, Wang Z. et al ( 2023 ) proposed a novel method that integrates an attention module with a capsule neural network, aiming to enhance P300 classification effectiveness. Zhang et al ( 2022b ) proposed an improved EEGNet model, which enhances the signal-to-noise ratio through xDAWN filtering and addresses sample imbalance with a focal loss function.…”
Section: Introductionmentioning
confidence: 99%
“…It has achieved good performance in both offline and online data. Wang Z. et al ( 2023 ) combined techniques such as Mixup, stochastic weight averaging, label smoothing, and focal loss during the training of deep learning methods so as to improve the performance of models such as EEGNet in the cross-subject P300 classification task. The single-scale convolution used by these methods may not be able to comprehensively extract the temporal and spatial features of P300.…”
Section: Introductionmentioning
confidence: 99%